INCIDENCE OF MYCOTOXINS IN MOULDY SMOKED DRIED FISH AND MEAT (KUNDI) MARKETED IN SOUTHWESTERN NIGERIA - Wambai, Fatima O.; Awotula, Olusola; Oyedele, Oluwapelumi A.; Ezekiel, Chibundu N.; Akintunde, Adeyinka O.; Tayo, Grace O. (Fungal Territory, 2021)
The mycotoxicological safety of 85 mouldy dried fish (n=40) and meat (n=45) samples purchased from Ijebu-ode, Ogun State and Aleshinloye, Ibadan, Oyo State markets both in South Western part of Nigeria respectively, was assessed due to heavy consumption of these animal protein sources by many low-income families in Nigeria. The presence of aflatoxigenic moulds and levels of aflatoxins in the samples were determined by the dilution plating technique and high performance thin-layer chromatographic method. The predominant fungal species isolated from the samples was Aspergillus niger-clade (49.65%); other species isolated include Aspergillus section Flavi (36.83%) and (13.52%). All samples analysed for mycotoxin presence were contaminated with aflatoxin B1. Aflatoxin B2, G1 and G2 were below detectable limits. About 13% of the samples had aflatoxin B1 concentration higher than the maximum acceptable level (10 ng/g). Results imply that the consumption of mouldy dried meat can result in serious public health hazard and hence there is need for advocacy programs to enlighten the populace on proper processing and storage of meat products.